Non-coaxial heterogeneous deformation in the Num orthogneiss (Arun valley, Mt. Makalu area, eastern Nepal) - Carosi, R; Frassi, C; Montomoli, C; Pertusati, PC; Groppo, C; Rolfo, F; Visonà, D (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1241 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.34